Design of a repetitive controller as a feed-forward disturbance observer - Tang, Mi; Formentini, Andrea; Odhano, S; Zanchetta, Pericle (2016)
From the structure point of view, a repetitive controller (RC) is considerably similar to a disturbance observer. By adding a correction term to the traditional RC and considering the disturbances as states, the repetitive controller can be designed in the same way as a disturbance observer. This paper presents therefore a new simple way of tuning a repetitive controller. Simulations show that, when compared with the traditional RC, the proposed RC configuration can achieve greater stability margin. As opposed to the traditional plug-in RC, the new RC structure studied in this paper is also shown to be robust against variations in the inner loop delays if it is used in a cascaded configuration. The immunity to plant parameter variations is another added benefit of the proposed controller.